Mechanical and microstructural characterization of fiber reinforced fly ash based geopolymer composites - Al-mashhadani, Mukhallad M.; Canpolat, Orhan; Aygormez, Yurdakul; Uysal, Mucteba; Erdem, Savas (ELSEVIER SCI LTD, 2018)
In this paper, an experimental investigation was carried out to study some mechanical and microstructural characteristics of fly ash based geopolymer mortars reinforced with three different fiber types. Steel, polypropylene, and polyvinyl alcohol fibers were used and the effect of their addition on the geopolymer composites behavior regarding strength properties, abrasion resistance, and drying shrinkage was studied, furthermore, a microstructural analysis was carried out to understand the geopolymeric matrix composition and its bonding to the fibers. Results showed that the addition of fibers improved the strength characteristics of the geopolymer composites, for instance, the existence of Steel and polyvinyl alcohol fibers increased the flexural strength of the geopolymer composite 31.45% and 39.84% respectively with respect to control sample. Moreover, all fiber reinforced geopolymer composites yielded a drying shrinkage of less than 400 microstrains and an abrasion resistance of less than 1 g. Microstructural analysis of the non-fibrous geopolymer control sample revealed a good degree of geopolymerization and the fibers yielded an acceptable interfacial bonding with the geopolymeric binder. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Geopolymer; Fly ash; Fibers; Abrasion resistance; Drying shrinkage; MIX DESIGN; STRENGTH; CONCRETE; STEEL; PERFORMANCE; SHRINKAGE; BEHAVIOR; Construction & Building Technology; Engineering; Materials Science